The Missionary-Colonial Forms of Marriages and Sexualities Within African Pentecostalism: A Sankofa-De-Colonial Perspective - Themba Shingange (Religions)
Looking retrospectively at pre-colonial African marriages and sexualities is critical in the urge to transform the contemporary narratives about marriage and sexuality within African Christian spaces. In Africa, marriage and sexuality had cultural, spiritual, and religious intersectionality. However, the advent of the missionary-colonial enterprise reconstructed the concepts of marriage and sexuality by imposing the supremacy of Christianity and Civilization agendas. Thus, Africans were compelled to discard their views of marriage and sexuality to comply with the prescripts of Christianity, baptism, and church membership. This paper used the Sankofa and Decolonial theories to investigate the perpetual influence of the 19th-century missionary-colonial enterprise within the contemporary African Pentecostal views of marriage and sexuality. It debunked the heterotopias of the born-again experience which propels the supremacy of Christianity and civilization agendas. The findings indicated that these agendas manifest in the form of hetero-monogamous aspirations of missionaries that undermined the African views of marriage and sexuality, thus, rendering them as demonic, backward, barbaric, and something to be forgotten. Lamentably, the same narrative has shaped the views of Pentecostal Christians within the contemporary African context. However, this has created a myriad of problems for both Africans and Christianity in Africa. In conclusion, the study emphasized the need to delink from Western conceptualizations by rethinking African marriages and sexualities. This could be done by revisiting pre-colonial African marriage systems and sexualities to challenge the current distorted narrative while embracing the positive elements of Christianity.